A MODEL OF COLLABORATIVE GOVERNANCE FOR RELIGIOUS EDUCATION BOOK ASSESSMENT PROGRAM - Perwira, Reza; Sri Rahayu, Neneng; Asropi, Asropi (International Journal of Business, Law, and Education, 2023)
The religious education book assessment (REBA) program is one of the national book governances in Indonesia implemented by the Ministry of Religious Affairs collaboratively. However, this program is considered to have not divided the functions of stakeholders appropriately in accordance with the concept of collaborative governance and national book regulations which are the responsibility of the government, private sector and community. The results show: (1) stakeholder functions are based on variable indicators of collaboration by dividing responsibility among six program implementation teams (verifiers, IT teams, book assessors, supervisors, supervisors, and instrument developers). (2) The collaboration model of this program refers to the principles of collaboration dynamics: face-to-face, motivational sharing, attractive communication, knowledge, and high adaptability. (3) Macro collaboration between the government, private sector, and community needs to be optimized to support REBA programs that are oriented towards producing religious education books that are suitable for use by the community.